2019
DOI: 10.1002/dta.2701
|View full text |Cite
|
Sign up to set email alerts
|

The risk of higenamine adverse analytical findings following oral administration of plumula nelumbinis capsules

Abstract: Higenamine is a β2‐agonist that has been included in the Prohibited List of the World Anti‐Doping Agency (WADA) since 2017. Meanwhile, it exists in plumula nelumbinis, a part of the lotus seed, and is commonly used as an ingredient in cuisines, herbal medicines, and nutritional supplements in China and other countries in East Asia. Therefore, an evaluation of the risk of an adverse analytical finding (AAF) of higenamine caused by plumula nelumbinis products is necessary in doping control. In this study, 14 vol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 16 publications
0
22
0
Order By: Relevance
“…Although pharmacokinetics studies on HG and methods for its detection have been very widely described over the last few years, most of these studies involved intravenous administration of HG. There are no pharmacokinetic data for orally‐administered and externally applied HG in experimental animals or humans, despite oral administration and external application being the major routes used for delivering traditional Chinese herbal medicines.…”
Section: Introductionmentioning
confidence: 99%
“…Although pharmacokinetics studies on HG and methods for its detection have been very widely described over the last few years, most of these studies involved intravenous administration of HG. There are no pharmacokinetic data for orally‐administered and externally applied HG in experimental animals or humans, despite oral administration and external application being the major routes used for delivering traditional Chinese herbal medicines.…”
Section: Introductionmentioning
confidence: 99%
“…Higenamine, or norcoclaurine, is an alkaloid acting as β 2 -agonist, whose misuse in sports is prohibited at all times [91][92][93]. Due to its natural occurrence in numerous plants such as Annona squamosa, Aconitum carmichaelii, Plumula nelumbinis, and Nelumbo nucifera, it is often found in pre-workout and fat-burner supplements.…”
Section: Other Substancesmentioning
confidence: 99%
“…Due to its natural occurrence in numerous plants such as Annona squamosa, Aconitum carmichaelii, Plumula nelumbinis, and Nelumbo nucifera, it is often found in pre-workout and fat-burner supplements. However, an unclear or missing labeling of the ingredients of such products has caused several cases of assumed inadvertent doping within the last years [91][92][93]. LC-MS analysis of different preparations neither listing higenamine or relevant plant extracts on their label yielded the alkaloid at concentrations of 0.02-14 mg/g.…”
Section: Other Substancesmentioning
confidence: 99%
“…Lotus seeds and their processed by-products are widely consumed over the world for their high concentration of physiologically active substances [36,37]. Yan et al evaluated the AAF risk associated with higenamine after the administration of lotus plumule capsules [38]; they revealed that oral administration of the capsule presented a high risk of an AAF for higenamine. All participants in their study received a specific commercial capsule, and urine specimens were collected once a day.…”
Section: Human Studymentioning
confidence: 99%